The role of planning budgets in analyzing deviations and controlling performance A case study in the Coca-Cola Soft Drinks Company - Rzgar Abdalah Sabr Jaff; Halkawt Esmail Mohammed Amin; Karwan Mohammed Fatih Jalal (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The budget is a future financial plan used as a planning and monitoring tool by comparing the planned performance with the actual performance of the activities of the company and determining the deviations between the plan and the actual and analysis deviations by the financial management of the company. That the budgets have a clear impact on the various private sector enterprises where companies prepare budgets for planning including the volume of sales and the cost of goods sold and all marketing and administrative expenses as well as planning cash budgets. Despite the fact that planning budgets are considered a tool to assist the administration in achieving its objectives, but most of the industrial companies rely on evaluating the performance on the actual results of the profit without comparison with the plan to determine the deviation in light of which determines the efficiency of the performance of the company. The problem of research in the next question is ( The departments of industrial companies compare the actual results with the planned budgets in order to correct deviations and control and assess performance?. The objective of the research is to achieve a practical approach that enables the financial management of companies to assess their financial performance by answering the following question (the extent to which the departments of the industrial companies compare the actual results of profit with the budget plan to address deviations, control and performance evaluation.The research hypothesis is that "the analysis of the results of the actual profit in the company (Coca-Cola) for the years (2013-2015) based on the planning budgets prepared by the company is considered a strong indicators to assess the efficiency of performance in the company."